Skeletal Muscle O-GlcNAc Transferase Action on Global Metabolism Is Partially Mediated Through Interleukin-15 - Zumbaugh, Morgan D.; Yen, Con-Ning; Bodmer, Jocelyn S.; Shi, Hao; Gerrard, David E. (Frontiers in Physiology, 2021)
Besides its roles in locomotion and thermogenesis, skeletal muscle plays a significant role in global glucose metabolism and insulin sensitivity through complex nutrient sensing networks. Our previous work showed that muscle-specific ablation of O-GlcNAc transferase (OGT) led to a lean phenotype through enhanced interleukin-15 (IL-15) expression. We also showed OGT epigenetically modified and repressed the Il15 promoter. However, whether there is a causal relationship between OGT ablation-induced IL-15 secretion and the lean phenotype remains unknown. To address this question, we generated muscle specific OGT and interleukin-15 receptor alpha subunit (IL-15r) double knockout mice (mDKO). Deletion of IL-15r in skeletal muscle impaired IL-15 secretion. When fed a high-fat diet, mDKO mice were no longer protected against HFD-induced obesity compared to wild-type mice. After 22-wks of HFD feeding, mDKO mice had an intermediate body weight and glucose sensitivity compared to wild-type and OGT knockout mice. Taken together, these data suggest OGT action is partially mediated by muscle IL-15 production. Our work suggests that interfering the OGT-IL15 nutrient sensing axis may provide a new avenue to combating obesity and its related metabolic disorders and provide some clarity into how the O-GlcNAc nutrient signaling pathway leads to a lean phenotype.